PENYULUHAN TANAMAN OBAT KELUARGA (TOGA) DI PULAU BELAKANG PADANG KOTA BATAM - Ditte Ayu Suntara; Afif D Alba, Fasida Dharma Yudastoro (Adiba Aisha Amira, 2022)
Toga stands for Medicinal Plants family. Family medicinal plants are essentially a piece of land either in the yard, garden or field that is used to cultivate medicinal plants in order to meet the family's need for medicines. Garden Medicinal plants or medicinal ingredients can then be distributed to the community, especially medicines derived from plants (Agriculture Service, 2018). Medicinal plants are essentially a plot of land, like a yard, garden or field that is used for the cultivation of medicinal plants for the purposes of the family as the first step when symptoms appear. The low level of community utilization of family medicinal plants as light first aid for younger families. Counseling here so that people are more motivated in empowering family welfare. After carrying out counseling activities regarding